The equity of school facilities funding: Examples from Kentucky. - William J. Glenn; Lawrence O. Picus; Allan Odden; Anabel Aportela (Arizona State University, 2009)
While there is an extensive literature analyzing the relative equity of state funding systems for current operating revenues, there is a dearth of research on capital funding systems. This article presents an analysis of the school capital funding system in Kentucky since 1990, using the operating-revenue analysis concepts of horizontal equity, vertical equity, and fiscal neutrality. In general one could tentatively conclude that Kentucky's capital-funding system was reasonably equitable until an expansion of district options in 2003-04 was followed by greater measures of inequity. This analysis points to specific methods for Kentucky to restore equity to its school capital funding structure as well as a model for analysis of other capital funding systems.